2009
DOI: 10.1093/aje/kwn399
|View full text |Cite
|
Sign up to set email alerts
|

Is Maternal Periodontal Disease a Risk Factor for Preterm Delivery?

Abstract: Several studies have suggested an association between maternal periodontal disease and preterm delivery, but this has not been a consistent finding. In 2006-2007, the authors examined the relation between maternal periodontal disease and preterm delivery among 467 pregnant Thai women who delivered a preterm singleton infant (<37 weeks' gestation) and 467 controls who delivered a singleton infant at term (> or =37 weeks' gestation). Periodontal examinations were performed within 48 hours after delivery. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 58 publications
1
33
0
7
Order By: Relevance
“…These results are in accordance with study conducted by Mokeem [22] who concluded that periodontal disease was more prevalent in mothers who delivered preterm low birth weight infants than in mothers who delivered full-term normal weight infants. This can be explained by the fact that periodontal disease may influence pregnancy outcome by direct or indirect effect of periodontal pathogens and inflammatory mediators on the developing fetus.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with study conducted by Mokeem [22] who concluded that periodontal disease was more prevalent in mothers who delivered preterm low birth weight infants than in mothers who delivered full-term normal weight infants. This can be explained by the fact that periodontal disease may influence pregnancy outcome by direct or indirect effect of periodontal pathogens and inflammatory mediators on the developing fetus.…”
Section: Discussionsupporting
confidence: 92%
“…Studies that have analysed the relation between periodontitis and adverse pregnancy outcomes have considered a variety of outcomes, such as preterm birth, low birthweight (<2500 g) or preterm low birthweight (Xiong et al 2007, Agueda et al 2008a). They have reported conflicting results (Dasanayake 1998, Bassani et al 2007, Clothier et al 2007, Santos‐Pereira et al 2007, Siqueira et al 2007, Vergnes & Sixou 2007, Xiong et al 2007, Agueda et al 2008a, b, Pitiphat et al 2008, Vettore et al 2008, Lohsoonthorn et al 2009, Michalowicz et al 2009, Srinivas et al 2009). The studies have been conducted among a variety of populations with very different rates of periodontitis or of adverse pregnancy outcomes, but frequently among small or deprived populations (Clothier et al 2007, Xiong et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A number of subsequent studies corroborated this association [810], although many other studies found no association [1114]. One systematic review on the subject concluded that additional longitudinal, epidemiological and interventional studies are required in order to establish whether or not there is a causal relationship between poor dental health and pregnancy outcome [15].…”
Section: Introductionmentioning
confidence: 99%